(untitled) (mathematica didactica, 2007)
This paper analyzes how and to what extent math teachers draw instructional conclusions from state mandated school performance tests that aim to encourage data-based school improvement. The interview study approached elementary and secondary school teachers (n = 50) in Baden-Württemberg, one of the larger German states. Mostly sobering results of the qualitative content analysis show that a single math test after a two-year learning period cannot provide sufficient information for better understanding students’ mathematical knowledge acquisition. Only a minority of the teachers explained that some test assignments prompted reflection about slightly changing their instructional approach. The paper concludes with a discussion on the characteristics of the testing and feedback system in Baden-Württemberg and its potential impact on the schools’ disapproval to make sensible use of the test results.